Comparative Toxicities of Hydrastis Canadensis L., Berberis aristata DC. and Achillea millefolium L. Against Brine Shrimps (Artemia salina) Using Dosage Mortality Curve: A Probit Approach - Mahwish Ahmed Karim,; Ghazala H. Rizwani,; Afaq Ahmed Sidddiqui ,; Muhammad Farhanullah Khan, (Journal of Basic & Applied Sciences, 2015)
Hydrastis canadensis, Berberis aristata DC. and Achillea millefolium were compared for their toxicities against brine shrimps (Artemia salina). After applying statistical method of probits to the experimental data, H. canadensis was found to be the most toxic with the LC50 of 3.236 mg/ml, while, B. aristata showed moderate toxic potential showing that of 60.264 mg/ml and A. millefolium manifested the highest value, that is, 41297.5 mg/ml.